Does Self-Efficacy Acts as Mediator in Entrepreneurial Intentions Development: A Case Study of Herbal City in Thailand - Siraphatthada, Yananda (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper aims to evaluate whether the self-efficacy mediates the entrepreneurial intention by considering the factors as risk propensity, entrepreneurial experience, gender and entrepreneurial experience in the context of Thailand. Quantitative method has been followed to assess the aim of the study. The instrument used for data collection is an ordinal scale based survey questionnaire. A sample of 300 entrepreneurs from Thailand was drawn from the population to ensure the authenticity and reliability of the data. Smart PLS has been used as the statistical medium from where the data was analysed. Confirmatory Factor Analysis, discriminant validity, and basic regression analysis have been carried out to assess the outcomes of the data. The results indicate that there is a direct impact of entrepreneurial education on the intention development. Moreover, all three enablers of self-efficacy i.e. entrepreneurial knowledge, entrepreneurial experiences, and risk propensity mediates the relationship between entrepreneurial education and intention. Collectively, the variable of self-efficacy also mediated the relationship between the two variables. The incorporation of qualitative data will allow the future researchers to provide more detailed discussion about the research topic by gaining the comprehensive information through interviews.